1983
DOI: 10.1111/j.1365-2265.1983.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heparin on Serum Free Thyroxine Linked to Post‐heparin Lipolytic Activity

Abstract: A possible association between free T4 (fT4) changes, occurring after heparin administration, and the post-heparin lipolytic activity, i.e., the release of lipases and the lipolysis of triglycerides to non-esterified fatty acids (NEFAs) was studied. In 19 patients heparin increased mean fT4 values obtained by equilibrium dialysis from 23.4 to 38.6 pmol/l (P less than 0.01) and mean fT4 values measured by GammaCoat two-step RIA from 17.0 to 24.1 pmol/l (P less than 0.01), the results of the two methods agreeing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…In chronically ill geriatric patients, we were able to demonstrate an increased THBI activity of the serum and its correlation to the clinical state but not to age. The well known effect of heparin on FT4 is also said to be mediated by a heparin‐induced excess of NEFA 14–17 . Interestingly, in hospitalized chronic geriatric patients, this heparin effect could be found even at small doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronically ill geriatric patients, we were able to demonstrate an increased THBI activity of the serum and its correlation to the clinical state but not to age. The well known effect of heparin on FT4 is also said to be mediated by a heparin‐induced excess of NEFA 14–17 . Interestingly, in hospitalized chronic geriatric patients, this heparin effect could be found even at small doses.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Nonthyroidal illness in geriatric patients may lead to changes in serum T4, FT4, T3, and TSH levels 9–11 . (3) The hormonal parameters of thyroid activity may be influenced, both in vitro and in vivo, by several drugs without thyroid hormone activity; for example, glucocorticoids 12 and dopamine 13 suppress TSH secretion, and the heparin‐induced excess of serum non‐esterified fatty acids (NEFA), 14–17 or furosemide, 18–19 competes for T4 binding in serum.…”
mentioning
confidence: 99%
“…Although free and total T4 can be normal or slightly reduced, it can sometimes be increased due to the effect of heparin used in anticoagulant therapy during HD. Lipolytic activity of heparin leads to lipolysis of triglycerides in non-esterified free fatty acids which in high concentrations compete with T4 for proteins carriers (13). TSH levels according to several study results in patients with CKD are not uniform.…”
Section: Introductionmentioning
confidence: 97%
“…Chu et al [5] could demonstrate only a 50% decrease of T3; free T3 and reverse T3 were not evaluated in their study. The normal fT4 concentrations during CPB are most likely mediated by the large amounts of heparin dur ing CPB [13,14]. Gotzsche et al [7] even found elevated fT4 concentrations during CPB.…”
Section: Influence O F Iodine Contamination On Thyroid Functionmentioning
confidence: 99%